2003
DOI: 10.1016/s0191-8869(03)00042-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and environmental relationship between Cloninger's dimensions of temperament and character

Abstract: The purpose of this study was to determine whether Cloninger's revised 7-factor model of personality showed incremental validity over his four dimensions of temperament. A sample of 2517 Australian twins aged over 50 between 1993 and 1995 returned completed self-reported measures of Self-directedness, Cooperativeness, and Self-transcendence from Cloninger's Temperament and Character Inventory. Many of these twins had participated in a 1988 study containing Cloninger's temperament measures of Harm Avoidance, No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(169 citation statements)
references
References 39 publications
(36 reference statements)
11
150
3
5
Order By: Relevance
“…As a genetic attribute distractiveness has an impact on temperament, i.e. novelty-seeking, harm avoidance and reward dependence (Cloninger, Svrakic, & Przybeck, 1993), and is likely to be modulated through childhood and adolescence as character is formed (Gillespie, Cloninger, Heath, & Martina, 2003;Joyce et al, 2003). From the results in the present investigation it is suggested that stress accentuates distractive behaviour.…”
Section: Predisposing Factorsmentioning
confidence: 52%
“…As a genetic attribute distractiveness has an impact on temperament, i.e. novelty-seeking, harm avoidance and reward dependence (Cloninger, Svrakic, & Przybeck, 1993), and is likely to be modulated through childhood and adolescence as character is formed (Gillespie, Cloninger, Heath, & Martina, 2003;Joyce et al, 2003). From the results in the present investigation it is suggested that stress accentuates distractive behaviour.…”
Section: Predisposing Factorsmentioning
confidence: 52%
“…The heritability of ' selfdirectedness ' is high and in several studies it may be even higher than that for the four temperament traits (Comings et al 2000 ;Ando et al 2002Ando et al , 2004Gillespie et al 2003 ;Isen et al 2009). However, little is known about the biology of character dimensions.…”
Section: Discussionmentioning
confidence: 97%
“…When all factors were considered together using a statistical tool called multivariate analysis, the genetic contribution to selftranscendence averaged 40 percent for both sexes. These results were unchanged by the time the size of this study had increased to 2,517 twins (Gillespie, 2003). Ando and colleagues, (2002; reported twin studies for 617 pairs of adolescent and young adult twins in Japan.…”
Section: Kirkmentioning
confidence: 71%